Bank Wakaf Mikro The Moderation Effect on Islamic Microfinance Preference in East Java - Rofiqoh, Siti Nur Indah; Sukmana, Raditya; rufaidah, Anik (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
There are many institutions in East Java Such as Sharia Kopwan, Baitul Maal Wat Tanwiil (BMT) and also Bank Wakaf Mikro (BWM), but they have many problems including the moderation effect. It caused by many factors like Islamic product design, Islamic product business and Islamic Good Governance implementation. The purpose of this study is to investigate the moderation effect of BWM in East Java. This paper was conducted qualitatively with a multiple case studies approach in six cash waqf institution in East Java. It was conducted that the moderation in BWM had similarities correction in product design management of fund, using ijaroh. The Islamic product business were chosen to the productive poor around the Islamic Boarding School and should to academic mission. Last, to upgrade Islamic good governance, BWM ought to collect the waqf funds directly, exclude LAZNAS BSM UMAT.